PENGARUH PENGGUNAAN SERAT DAUN NANAS DALAM PEMBUATAN KOMPOSIT MENGGUNAKAN METODE VACUM BAGGING TERHADAP KEKUATAN TARIK DAN BENDING - Muhammad Iqbal Aizi Iqbal; Sehono; Ferry Setiawan (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2022)
Natural fiber is a type of raw material for the manufacture of yarn or fabric that has an origin from animals or plants that go through geological processes. This natural fiber has properties that tend to be easily weathered but there are advantages, namely having advantages in providing comfort for humans. Pineapple fruit, which used to be used only as a food ingredient or jam, is now a fairly important raw material. Therefore, nowadays the development of composite technology leads to natural fiber composites (organic) subject to renewable properties so as to reduce environmental disturbances. In this study, a composite of pineapple fibers with immersion variations and without immersion in NaCl solution was carried out. Tensile and bending tests are carried out to determine the mechanical characteristics of the Soaking treatment of NaCl. Based on the results of tensile testing by conducting Immersion NaCl raises the mechanical strength of the composite. At Immersion NaCl tensile strength reaches 35.02 MPa, while non-soaked ones have a tensile strength of 26.29 MPa. In bending testing specimens with immersion treatment using NaCl also which has the largest bending strength, namely 6,137,722.00 MPa while without immersion it has a value of 5,406,494.61 MPa.